Evaluation of Sterilization using the MEH200® (Cotton Pack) in Vascular Access Puncture. Issue 10 (November 2015) - Ueda, Yuka; Tsuchida, Kenji; Okada, Daigo; Muromiya, Yasuto; Suenaga, Takehiro; Yokota, Narushi; Kawahara, Kana; Nagai, Kojiro; Kanayama, Hiro-omi; Minakuchi, Jun
Background: In recent years, chlorhexidine-alcohol has been attracting increasing attention for its role in skin antisepsis. There have been few reports on the infection frequency associated with vascular access and no reports on the infection frequency associated with antiseptics. Aims: We investigated skin disinfection during vascular access puncture in patients on chronic hemodialysis (HD). Methods: We analyzed patients on chronic HD with arteriovenous fistula (AVF) and arteriovenous graft (AVG) between January 2006 and December 2010. Results: The MEH200® (cotton pack including alcohol and chlorhexidine gluconate) was used in 97% of patients. A total of 1130 patients were analyzed, including 911 with AVF and 219 with AVG. Of these, seven with AVF had an infection attributed to the insertion site, which represented a rate of 0.008% of patients per year. Twenty patients with AVG had an infection attributed to the insertion site, which represented a rate of 9.1% of patients per year. The frequency was not higher than that previously reported. Conclusions: In HD patients, the MEH200® may be effective for the prevention of bacteremia.